The effect of breeder body mass on laying performance, egg quality, and hatching traits of Japanese quail. - Busra Ozkan; Nasir Abdallah; Yunus E. Boga; Kadriye Kursun; Mikail Baylan (Spanish Journal of Agricultural Research)
Aim of study: The aim of this research was to determine the effect of breeder body mass on egg laying performance, egg quality, and hatching traits of Japanese quail (Coturnix japonica).